The Effect of Giving One Egg Per Day on Stunted Children Aged 2-5 Years in Buton Regency on Zinc Levels - Saputro, Alvreyna Cherienda Laviashna; Gunarti, Dwirini Retno (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Despite can be prevented with good nutrition, average prevalence of stunting in Indonesia remains high at 30.8%. The effects of stunting are detrimental to the individual and Indonesia's human resources. Stunted children had low blood zinc levels which disrupted enzyme and antioxidant activity, as well as bone growth processes and bone homeostasis. Eggs that contain zinc and have high bioavailability are expected to be able to increase low blood zinc levels. This study was designed to examine the impact of routine egg consumption on zinc levels in stunted children. Methods: This experimental quantitative study was conducted in the Siontapina Health Center, Buton Regency, Southeast Sulawesi. and included 22 participants which divided into intervention and control groups. The intervention was carried out by health workers giving one egg per day for 30 days with the same type of cooking per day to the participants. Zinc levels were assessed using a spectrophotometer and analyzed using statistical software. Result: The results showed a significant difference between the two groups (p <0.05). The average zinc level in the intervention group was 718.8133 ug/dL, which was higher than the control group (143.4536 ug/dL). Thus, giving 1 egg a day for 30 days caused a significant change in blood zinc levels in stunted children aged 2-5 years in Buton Regency. Conclusion: Stunted children supplemented with one egg daily for 30 days had significantly higher zinc levels than unsupplemented children.